(NsO^INENIQ (B/s - (NgRIBOEDOW(B, (NaLEKSANDRs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1988)
(Nw TOM WO[LI WSE ZNA^ITELXNYE LITERATURNYE PROIZWEDENIQ a(B. (Ns(B. (NgRIBOEDOWA (B("(NgORE OT UMA(B", (NDRUGIE DRAMATI^ESKIE PROIZWEDENIQ(B, (NSTIHOTWORENIQ(B, (NPROZAI^ESKIE OPYTY(B, (NSTAI(B), (NA TAKVE EGO PISXMA(B.rus
rus
Keywords: (NdRAMAs; (NsTIHOTWORENIQs; (NsTATXIs